1988
DOI: 10.1128/aac.32.10.1583
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity relationships of selected phenazines against Mycobacterium leprae in vitro

Abstract: Structure-activity relationships of phenazines against Mycobacterium leprae were investigated by using an in vitro radiorespirometric assay. In general, activity in ascending order was observed in compounds containing no chlorine atoms, a monochlorinated phenazine nucleus, and chlorines in the para positions of both the anilino and phenyl rings. The most active compounds contained a 2,2,6,6-tetramethylpiperidine substitution at the imino nitrogen. Most of these chlorinated phenazines were considerably more act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…We have employed radiorespirometry to evaluate a variety of macrolides (6) and clofazimine derivatives (7,8). In addition, we have recently demonstrated that the BACTEC 460 system can also be used in the radiorespirometric assessment of drug activity against M. Ieprae in the absence of increases in cell numbers (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have employed radiorespirometry to evaluate a variety of macrolides (6) and clofazimine derivatives (7,8). In addition, we have recently demonstrated that the BACTEC 460 system can also be used in the radiorespirometric assessment of drug activity against M. Ieprae in the absence of increases in cell numbers (5).…”
mentioning
confidence: 99%
“…M. leprae was harvested from the footpads of nude mice as previously described (6,7). Briefly, footpads containing approximately 1010 acid-fast bacilli were surface decontaminated with iodine and ethanol, minced with scissors, and homogenized in Middlebrook 7H9 broth containing 1% (wt/vol) bovine serum albumin.…”
mentioning
confidence: 99%
“…Among these was the use of a Buddemeyer-type detection system to measure 14CO2 production from [1-14C]palmitic acid by M. leprae in an axenic medium (1). This system is very sensitive, and its simplicity has facilitated screening of a variety of macrolides (3), clofazimine derivatives (4,5), and fluoroquinolones (S. G. Franzblau ) consists of (final concentrations) polymyxin B (50 U/ml), amphotericin B (5 pg/ml), nalidixic acid (20 pug/ml), trimethoprim (5 jig/ml), and azlocillin (10 ,ug/ml). Susceptibility testing.…”
mentioning
confidence: 99%
“…We have previously demonstrated the utility of radiorespirometry in evaluating the in vitro activities of a variety of macrolides (9), fluoroquinolones (11), phenazines (10,12), and aminoglycosides, lincosamides, and rifamycins (7) against M. leprae in axenic media with either a Buddemeyertype detection system (5) or the BACTEC 460 instrument (6) as a means of assessing drug activity in the absence of bacterial multiplication. We and our colleagues have also used assays quantitating phenolic glycolipid-1 synthesis and adenosine triphosphate concentration (8) as indices of drug activity against both extracellular (16) and intracellular (20) M. leprae.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro screening for drugs active against the uncultivable leprosy bacillus can be performed by radiorespirometric analysis of viable Mycobacterium leprae freshly harvested from nude mice (5)(6)(7)(9)(10)(11)(12). In vitro systems have many advantages over the traditional mouse footpad system (22), especially with regard to time, expense, quantity of drug required, and independence of mouse pharmacokinetics.…”
mentioning
confidence: 99%